Combined effect of the smartphone addiction and physical activity on the depressive symptoms in secondary school students: a cross sectional study in Shanghai, China - Yang, Rui; Tan, Shuoyuan; Abdukerima, Gulqihra; Lu, Ting; Chen, Chen; Song, Lixin; Ji, Bing; Lv, Yipeng; Shi, Jianwei (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to investigate the prevalence of smartphone addiction, physical activity levels, and depressive symptoms among secondary school students, and to analyze the combined impact of smartphone addiction and physical activity on depressive symptoms.MethodsA cluster sampling method was employed in two secondary schools in the Jing’an District of Shanghai, China. Univariate analysis was used to compare the prevalence of depressive symptoms across different demographic characteristics. Logistic regression was utilized to examine the associations between smartphone addiction, physical activity, and their combined effect on depressive symptoms.ResultsA total of 1,316 respondents participated in the study, with reported prevalence rates of depressive symptoms (36.2%), smartphone addiction (19.2%), and insufficient physical activity (23.3%). Risk factors for depressive symptoms included being a non-only child (OR=1.421, 95% CI: 1.090-1.853, P=0.009), inadequate sleep duration (OR=2.722, 95% CI: 2.070-3.578, P<0.001) and smartphone addiction (OR=2.173, 95% CI: 1.621-2.913, P < 0.001). Adolescents with smartphone addiction were significantly more likely to report depressive symptoms compared to those without (OR=2.173, 95% CI: 1.621-2.913, P < 0.001). Joint analysis indicated that combined smartphone addiction and insufficient physical activity significantly increased the risk of depressive symptoms (OR=2.781, 95% CI: 1.627-4.753, P < 0.001).ConclusionThe study identified a high prevalence of severe smartphone addiction, insufficient physical activity, and elevated rates of depressive symptoms among secondary school students. Smartphone addiction and inadequate physical activity were associated with increased likelihood of depressive symptoms. Moreover, higher levels of physical activity appeared to mitigate the adverse impact of smartphone addiction on depressive symptoms.